2000
DOI: 10.2190/8kk2-wyt7-gj2n-y7r5
|View full text |Cite
|
Sign up to set email alerts
|

Risking the Future: Unprotected Intercourse and HIV/AIDS Knowledge among Female Commercial Sex Workers in Central Bangladesh

Abstract: This study examined levels of AIDS knowledge and condom practices in a sample of female commercial sex workers (CSWs) in Bangladesh. The 284 subjects were questioned about AIDS knowledge using a 12-item AIDS knowledge and patterns of condom use questionnaire. The subjects had a moderate knowledge of AIDS with 61.5 percent of the sample responding correctly to 6 or more of the 12 AIDS knowledge questions. Those with high levels of AIDS knowledge used condoms at a higher rate than those with low levels of AIDS k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Despite these limitations, some researchers still maintain that addressing these variables is an appropriate role for health education [26]. In several studies it has been found that socio-demographic variables are related to the various health behaviors [8,17,23,[27][28][29][30][31][32]. Some community psychologists [27] have used HBM variables as a base for developing educational and BCC strategies and intervention programs.…”
Section: Socio-demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, some researchers still maintain that addressing these variables is an appropriate role for health education [26]. In several studies it has been found that socio-demographic variables are related to the various health behaviors [8,17,23,[27][28][29][30][31][32]. Some community psychologists [27] have used HBM variables as a base for developing educational and BCC strategies and intervention programs.…”
Section: Socio-demographic Factorsmentioning
confidence: 99%
“…They are based on a grab bag of models and constructs that may or may not alter risk behavior (cited in [8]). Knowledge or education alone does not change behavior and neither does the teaching of necessary skills alone [8,29]. Public health consequences resulting from ill waste management or handling of infectious waste, are not simply health problems.…”
Section: Expectationsmentioning
confidence: 99%
“…A number of contextual, biomedical, and behavioral factors, which can speed up HIV prevalence, are widespread in Bangladesh. These are: sharing common borders with India and Myanmar, which are high HIV prevalent countries; close contact among different "core" populations (sex workers, injecting drug users), "bridging" populations (rickshaw pullers, long-distance truckers, and increasing numbers of men having sex with men), and the general population; existence of a sizeable (approximately 105,000) population of sex workers (SWs) with high rate of client contact per week and low use of condoms; prevalence of other sexually transmitted infections (STIs) including highly active syphilis among different population groups, particularly SWs; increased number of intravenous drug users with high rate of needle sharing; lack of biomedical safety, i.e., lack of HIV screening in blood transfusion and high contribution of professional blood donors to the total blood supply of the country, of whom many are injecting drug users; transport workers, mostly long-distance truckers who are living away from their wives; and high rate of international migration of labor to and from countries with HIV epidemics [3,5,10,11,[14][15][16][17][18][19].…”
Section: Situation Of Hiv and Aids And Young Adult's Vulnerability Inmentioning
confidence: 99%
“…These two groups of population are high risk takers for HIV and AIDS as they like to experiment with new things, whether sex or drugs [2]. Several studies have been conducted to explore the risky sexual behavior of adolescents and youths [2][3][4][5][6][7][8]. These studies revealed that a large number of youths go to sex workers for buying and experimenting with sex and most of them do not use condoms, which signifies the vulnerability of the young adults and students to sexually transmitted diseases (STDs) including HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the frequency of pre-marital and extra-marital sex and the large number of sexual acts with sex workers are commonly known factors associated with the transmission of HIV in Bangladesh [9,10]. Among the general population, approximately 10% of men reported having bought sex from female sex workers [11].…”
Section: Introductionmentioning
confidence: 99%